'Every movement floating, every voice echo-like': Villette as a Cinematic Text. (1st October 2020) - Choe, Jian
Abstract : This article aims to reappraise Villette as a proto-cinematic text, considering the images and techniques of the motion picture as shown in the novel. Published in 1853 prior to the advent of film, Villette was not consciously influenced by the new medium. Yet the key aspects of its form and content, including its fractured structure, temporal discontinuity, camera-eye presentation and urban modern themes, represent an innovative mode of writing, which was to be called 'cinematic' half a century later. The novel thus predates the literary appropriation of cinematography that proliferated from the early twentieth century onwards. The presence of film qualities in Villette indicates that Charlotte Brontë fashioned an experimental modern aesthetic in her final masterpiece, envisioning the world with new eyes and anticipating a new art of the coming century.